Cooperation in the Nile Basin : Sharing and Using Knowledge to Improve Water Resource Management - World Bank Group (World Bank, Entebbe, 2016)
The countries of the Nile Basin have been working together for the past 15 years to build a program of cooperation that allows them to utilize their shared resource equitably for regional economic development. Through the Nile Basin Initiative (NBI), they have generated extensive, impartial knowledge and information about the river basin. Developing a common understanding of the river system has been crucial for building trust among the countries. Today, this knowledge is embedded in accessible information systems, informing planning, policies, and projects that are set to improve opportunities for economic growth across the region.